Evaluation of antioxidant and chemopreventive effect of Cocos nucifera L. (Jahangirnagar University Journal of Biological Sciences, 2018)
This study revealed the antioxidant and anticancer activities of the ethanolic extract of the tender fruits of Cocos nucifera. In antioxidant screening, IC50 value was found to be 7.71μg/mlfor ascorbic acid and44.67 μg/ml for C. nucifera fruits. The phenolic content, total flavonoid and total tannin content were 537.89 mg GAE/100 gm, 40.69mg of QE/100 gm and 44.61 mg of GAE/100 gm of dry powder of C. nucifera respectively. In DMBA and croton oil-induced skin cancer in model mice,the extract significantly decreased the number, size, yield and burden of tumor when compared with carcinogenic control. The extract increased the level of natural antioxidants like GSH, SOD and Catalase. Moreover, substantial decrease in SGPT, SGOT (liver activity marker) was observed at different doses ofthe crude extract. Lipid profile of mice treated with C. nucifera was brought back to normal level to some extent when compared to carcinogenic control. In conclusion,C. nucifera fruits have antioxidant activity as well as preventive role on cancer initiation and propagation without major toxicity.Jahangirnagar University J. Biol. Sci. 6(2): 47-58, 2017 (December)